The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1983
DOI: 10.1111/j.1749-7345.1983.tb00083.x
|View full text |Cite
|
Sign up to set email alerts
|

EXAMINATION OF SPERMATOPHORE PRODUCTION BY LABORATORY‐MAINTAINED LOBSTERS (Homarus)

Abstract: Lobster aquaculture requires control of reproductive processes. We have previously described an electrical stimulation technique for collecting spermatophores from living lobsters (Homarus americanus). These spermatophores can potentially be used in a variety of ways including: 1) experimental manipulation of sperm, 2) artificial insemination of females, 3) sperm banking, and 4) evaluation of sperm production by the male. In this study, we evaluated spermatophore production and extrusion from: 1) laboratory re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Currently, it is difficult to ascertain the threat posed to European lobster stocks from hybridisation with H. americanus, since conflicting information exists as to both the likelihood of interspecific mating and the fertility of resultant hybrids. Talbot et al 21 found that the spermatophores of captive-reared hybrid males lacked sperm, suggesting that they were infertile, but Kitaka (pers comm., as cited by 22 ) achieved interspecific mating in captivity and asserted that both sexes of the resultant hybrid offspring were fertile. Fertile hybrids enable backcrossing and pervasive population-level introgression, although hybridisation is still a conservation threat even where hybrids are infertile, since it represents wasted reproductive effort 5,6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, it is difficult to ascertain the threat posed to European lobster stocks from hybridisation with H. americanus, since conflicting information exists as to both the likelihood of interspecific mating and the fertility of resultant hybrids. Talbot et al 21 found that the spermatophores of captive-reared hybrid males lacked sperm, suggesting that they were infertile, but Kitaka (pers comm., as cited by 22 ) achieved interspecific mating in captivity and asserted that both sexes of the resultant hybrid offspring were fertile. Fertile hybrids enable backcrossing and pervasive population-level introgression, although hybridisation is still a conservation threat even where hybrids are infertile, since it represents wasted reproductive effort 5,6 .…”
Section: Discussionmentioning
confidence: 99%
“…Although concerns that pathogenic syndromes of H. americanus may spread to devastate H. gammarus stocks have been tempered by the latter's apparent disease resilience 18,19 , fears that American lobster introductions may impact European populations through competition and genetic introgression have not been so readily mitigated, particularly following recent observations that Americans both predate on and interbreed with European counterparts 20 . Reports of wild hybridisation are concerning as well as surprising; while long established that Homarus hybrids could be bred in captivity through induced fertilisation 21 , it was also proposed that behavioural characteristics of sexual selection should constrain interspecific mating in the wild 22 . However, this appears not to be the case 20 .…”
mentioning
confidence: 99%
“…The most successful crossings appear to be American male with European female. The pure strains and produced hybrids have been used in numerous other experiments related to survival, growth, aggression, oxygen binding, egg quality etc (Gruffydd et al, 1975;Anon, 1978;Carlberg et al, 1978Carlberg et al, , 1979Mickelsen et al, 1978;Talbot et al, 1983Talbot et al, , 1984Harper & Talbot, 1984;Zalgalcky, 1985;Zalgalcky & Tidmarsh, 1985). The overall conclusion from several of these studies is that hybrid progeny show intermediate traits, rather than dominance of one parental type.…”
Section: Discussionmentioning
confidence: 99%
“…120 Hybrid males of H. americanus and H. gammarus were able to extrude spermatophore (about 71-80%) using an extrusion technique with electrical stimulation, but the spermatophore lacked sperm despite having a morphologically normal wall (a white sperm mass was not visible in any of the hybrid spermatophore examined microscopically) and the hybrid females may produce fertile eggs if back-crossed. 127 In hybridization H. gammarus  H. americanus, pure breed and hybrid offspring reached the post-larval stage in approximately the same time but the larvae of H. gammarus and hybrids were larger than those of H. americanus. A 1-year comparison of growth and survival revealed no significant differences in the size attained by juveniles of the two lobster species or their hybrids.…”
Section: Hybridization In Crayfish and Lobstermentioning
confidence: 97%
“…The findings suggest that European lobsters can recognize conspecific mates, possibly through chemical signals, and that these signals act as pre‐mating barriers, preventing hybridization 120 . Hybrid males of H. americanus and H. gammarus were able to extrude spermatophore (about 71–80%) using an extrusion technique with electrical stimulation, but the spermatophore lacked sperm despite having a morphologically normal wall (a white sperm mass was not visible in any of the hybrid spermatophore examined microscopically) and the hybrid females may produce fertile eggs if back‐crossed 127 . In hybridization H. gammarus × H. americanus , pure breed and hybrid offspring reached the post‐larval stage in approximately the same time but the larvae of H. gammarus and hybrids were larger than those of H. americanus .…”
Section: Hybridization In Decapod Crustaceanmentioning
confidence: 99%